2022
DOI: 10.21883/sc.2022.01.53028.9642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nickel on the lifetime of charge carriers in silicon solar cells

Abstract: It has been shown experimentally that nickel clusters on the surface of a silicon sample contain a large amount of oxygen and recombination impurities --- Cu, Fe, Cr, and so shows good gettering properties of clusters. The optimum temperature of nickel diffusion into silicon is determined as 800-850oC. Doping with impurity nickel atoms with the formation of clusters makes it possible to increase the lifetime of nonequilibrium charge carriers in the base of a solar cell by up to 2 times, while the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Gallium-phosphorus binary complexes, forming in rather large concentrations, can significantly affect the electrophysical, optical and photovoltaic properties of silicon. Estimation of this influence requires an integrated study of materials having rather a high concentration of molecular complexes such as Si 2 Ga − P + in the silicon lattice [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Gallium-phosphorus binary complexes, forming in rather large concentrations, can significantly affect the electrophysical, optical and photovoltaic properties of silicon. Estimation of this influence requires an integrated study of materials having rather a high concentration of molecular complexes such as Si 2 Ga − P + in the silicon lattice [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Then p−n junction was produced by phosphorus diffusion towards the " nickel" side of the wafer at T = 1000 • C during t = 30 min. After the diffusion, additional thermal annealing was carried out at the optimum temperature [16] T = 750−800 • C during t = 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported in [14][15][16][17][18][19] that doping of silicon SC with impurity nickel atoms ensures the improvement of SC performance. However, radiation hardness of such SCs has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The studies [9][10][11][12][13] showed, that doping of a siliconbased photocell with impurity nickel atoms by diffusion method leads to an improvement in its efficiency due to the gettering properties of nickel clusters. However this method (diffusion doping of silicon with nickel) to improve the photocell parameters requires several technological operations, such as chemical cleaning before and after nickel diffusion, nickel spraying (or nickel chemical deposition), diffusion annealing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However this method (diffusion doping of silicon with nickel) to improve the photocell parameters requires several technological operations, such as chemical cleaning before and after nickel diffusion, nickel spraying (or nickel chemical deposition), diffusion annealing, etc. [5,7,9].…”
Section: Introductionmentioning
confidence: 99%